Conductive poly(ε‐caprolactone)/polylactic acid scaffolds for tissue engineering applications: Synergy effect of zirconium nanoparticles and polypyrrole. (11th January 2022) - Jafari, Aliakbar; Mirzaei, Hadis; Shafiei, Mir Alireza; Fakhri, Vafa; Yazdanbakhsh, Amirhosein; Pirouzfar, Vahid; Su, Chia‐Hung; Ghaffarian Anbaran, S. Reza; Khonakdar, Hossein Ali
Abstract: Biocompatible and electrically conductive porous scaffolds with a desirable hydrophilicity and degradation rate and suitable mechanical performance are highly favorable for tissue engineering and regenerative medicine applications. In this study, we fabricated three‐dimensional (3D) porous bioscaffolds from poly(ε‐caprolactone) and polylactic acid containing different concentrations of zirconia nanoparticles (n‐ZrO2 ) through freeze‐drying technique. Afterward, the surface of the scaffolds was coated with an electrically conductive layer through in situ polymerization of polypyrrole (PPy) on the samples. Bioscaffolds exhibited a favorable range of mechanical properties and electrical conductivity, meeting the required mechanical performances and conductivity for a broad range of tissue engineering applications. Coating PPy on the scaffolds resulted in significantly higher hydrophilicity and faster biodegradation rate, as well as a noticeable enhancement on the in vitro cell attachment, proliferation, and viability. Our findings indicated that the simultaneous presence of n‐ZrO2 and PPy in the system presents a noticeable synergistic effect in overall properties and introduces the fabricated 3D porous scaffolds as promising candidates for tissue engineering and regenerative medicine applications.